2020
DOI: 10.1177/1071100720952075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexamethasone in Peripheral Nerve Blocks on Recovery of Nerve Function

Abstract: Background: Peripheral nerve blocks (PNBs) have revolutionized distal extremity surgery reducing pain and improving hospital efficiency. Perineural dexamethasone has been administered with PNBs to prolong their effects, although the safety of dexamethasone has not been established in the literature. This study aimed to determine if the addition of dexamethasone affected the postoperative neurological sensory status for foot and ankle surgeries and the recovery of nerve injuries. We hypothesized that the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Current clinical studies have not yet found that the use of dexamethasone peripherally causes long-term neurological injury. 35,36 In animal models, no nerve cell death was detected when dexamethasone was administered peripherally. 37,38 Therefore, cautious use was recommended by Baeriswyl et al 39 Further clinical observation and studies are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical studies have not yet found that the use of dexamethasone peripherally causes long-term neurological injury. 35,36 In animal models, no nerve cell death was detected when dexamethasone was administered peripherally. 37,38 Therefore, cautious use was recommended by Baeriswyl et al 39 Further clinical observation and studies are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…As dexamethasone could prolong the analgesic duration by inducing vasoconstriction, it has been used in peripheral nerve block as an adjuvant [148]. By contrast, a recent study reported a twofold increased risk of persistent neurologic symptoms when perineural dexamethasone was applied after foot and ankle surgery [149] (Table 1). Besides, dexamethasone is widely used in clinics for alleviating cerebral edema.…”
Section: Nervous Systemmentioning
confidence: 99%
“…Gagne (2021) expands on the Cochrane review and examines nerve deficits beyond one month after surgery. The results of the Gagne (2021) study show that 62% of dexamethasone recipients had a nerve deficit, and 59% of the ropivacaine-only PNB patients had a nerve deficit at the two-week visit (42). At the six-month follow-up visit, 65% of the patients that had a nerve deficit in the dexamethasone group had not fully recovered, and 40% of the ropivacaine-only nerve deficit group had not recovered.…”
Section: Dexamethasonementioning
confidence: 99%
“…At the six-month follow-up visit, 65% of the patients that had a nerve deficit in the dexamethasone group had not fully recovered, and 40% of the ropivacaine-only nerve deficit group had not recovered. The Gagne (2021) study shows "a 2-fold increased risk of delayed recovery when perineural dexamethasone was used as an adjunct" (42). Due to potential neurotoxicity and an inadequate understanding of the mechanism of action of dexamethasone, intravenous administration is preferable (43).…”
Section: Dexamethasonementioning
confidence: 99%